2004
DOI: 10.1002/pi.1493
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of elastomeric polypropylene by nanoclay fillers

Abstract: Polypropylene (PP) was prepared by metallocene catalysts so as to have a stereoblock structure, with isotactic sequences long enough to give crystallites functioning as crosslinks, but small enough in number to have the atactic chains predominate in a surrounding elastomeric matrix. The resulting thermoplastic elastomer was then blended with organically modified clays to document the conditions required to exfoliate the clay layers in a way to maximize the chances for good reinforcement. Some experiments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…[5][6][7][8][9]11,67,68 According to Deshmane et al, 10 the nucleating effect of MMT on polypropylene is high, whereas polyethylene remains almost unaffected. The addition of 4% MMT to polypropylene reduces the spherulite diameter from 210 to 14 μm, whereas the spherulite size of polyethylene remains unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9]11,67,68 According to Deshmane et al, 10 the nucleating effect of MMT on polypropylene is high, whereas polyethylene remains almost unaffected. The addition of 4% MMT to polypropylene reduces the spherulite diameter from 210 to 14 μm, whereas the spherulite size of polyethylene remains unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors claim that the disappearance of the silicate reflection after processing is accompanied by complete exfoliation. [11][12][13][22][23][24][25][26][27][28] Other researchers, however, showed that this is definitely not the case and an intercalated structure was also observed when the silicate reflection was absent from the XRD trace. [29][30][31] In his excellent paper, Vaia and Liu [32] analyzed the factors influencing XRD traces and pointed out the difficulties of quantitative or even qualitative analysis of nanocomposite structures.…”
Section: Introductionmentioning
confidence: 91%
“…[8][9][10][11][12][13] However, to really utilize all the potential advantages of polymer/layered silicate nanocomposites, the silicate must be exfoliated to a large extent into individual layers. For optimum performance the platelets should be distributed uniformly in the polymer matrix with an orientation parallel to the external load and they should strongly adhere to the polymer for efficient stress transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews summarize [36] that modifications of the MMT are predominantly focusing on an improvement of the compatibility between the clay and the polyolefin. What is often not taken into account is, that many phyllosilicates nucleate [714] PP extremely well. An altered nucleation may change the resulting semicrystalline structure considerably [1519].…”
Section: Introductionmentioning
confidence: 99%